207k views
4 votes
If f(x) = 2x - 5 and g(x) = x^2 - 4x-8 , find (f+g) (x)

(please do not just input answer without reasoning )

MY OPTIONS :

A. (f + g) ( x) = x^2 + 2x - 3


B . (f + g) ( x) = x^2 - 2x - 13


C. (f + g) ( x) = 3x^2 - 4x - 13


D. (f + g) ( x) = x^2 - 2x - 3

1 Answer

4 votes

We know that According to Algebra of Real Functions :

If f and g are two real functions which are defined under the same domain then (f + g)(x) = f(x) + g(x)

Given : f(x) = 2x - 5 and g(x) = x² - 4x - 8

⇒ (f + g)(x) = f(x) + g(x) = (2x - 5) + x² - 4x - 8

⇒ (f + g)(x) = f(x) + g(x) = x² - 2x - 13

Option B is the Answer

User Elou
by
6.1k points